Preliminary studies of new strains of trametes sp. from Argentina for laccase production ability - Fonseca, Maria Isabel (2015)
Oxidative enzymes secreted by white rot fungi can be applied in several technological processeswithin the paper industry, biofuel production and bioremediation. The discovery ofnative strains from the biodiverse Misiones (Argentina) forest can provide useful enzymesfor biotechnological purposes. In this work, we evaluated the laccase and manganese peroxidasesecretion abilities of four newly discovered strains of Trametes sp. that are nativeto Misiones. In addition, the copper response and optimal pH and temperature for laccaseactivity in culture supernatants were determined.The selected strains produced variable amounts oflaccase and MnP; whenCu2+ was added,both enzymes were significantly increased. Zymograms showed that two isoenzymes wereincreased in all strains in the presence of Cu2+. Strain B showed the greatest response toCu2+ addition, whereas strain A was more stable at the optimal temperature and pH. StrainA showed interesting potential for future biotechnological approaches due to the superiorthermo-stability of its secreted enzymes.